Invisible-hand explanations - Nozick, Robert (American Economic Review, 1994)
In Nozick (1974), I described how, if people entered into mutual protection agreements and firms offered buyers protective services, a dominant protection agency would arise by legitimate steps, and this would constitute at least an ultra-minimal state. No one need have intended to produce a state. A pattern or institutional structure that apparently only could arise by conscious design instead can originate or be maintained through the interactions of agents having no such overall pattern in mind. Following Adam Smith, I termed such a process or explanation an invisible-hand process or explanation and offered a list of examples to make the phenomenon salient. These included evolutionary explanations of the traits of organisms and populations, microeconomic explanations of equilibria, Carl Menger's explanation of how a medium of exchange arises, and Thomas Schelling's model of residential segregation. (Edna Ullmann-Margalit [1978] is a later attempt to define the concept.) Two types of processes seemed important: filtering processes wherein some filter eliminates all entities not fitting a certain pattern, and equilibrium processes wherein each component part adjusts to local conditions, changing the local environments of others close by, so the sum of the local adjustments realizes a pattern. The pattern produced by the adjustments of some entities might itself constitute a filter another faces. The opposite kind of explanation, wherein an apparently unintended, accidental, or unrelated set of events is shown to result from intentional design, I termed a hidden-hand explanation. The notion of invisible-hand explanation is descriptive, not normative. Not every pattern that arises by an invisible-hand process is desirable, and something that can arise by an invisible-hand process might better arise or be maintained through conscious intervention. Economics typically explains patterns in terms of the actions of rational agents. However, a disaggregated theory of the agent herself, wherein patterns that seem to indicate a central and unified directing agent are instead explained as the result of smaller, non-agent entities interacting, also might count as an invisible-hand explanation.1 The definitional details of what counts as invisible hand are less interesting than the particular theories.2 Time preference seems susceptible to evolutionary explanation (see Nozick, 1977; and Nozick, 1993 pp. 14-15). The future is uncertain, an organism may not survive to reap an anticipated reward, or the world might not present it. Innate time preference